EFEKTIVITAS PENGEMBANGAN USAHA EKONOMI PEREMPUAN (KAJIAN USAHA JAHITAN DI GAMPONG COT SEURANI MUARA BATU KABUPATEN ACEH UTARA) - Risna Dewi (Program Studi Administrasi Bisnis, 2021)
Study of the efficiency of women's economic enterprise growth in Cot Seurani Muara Batu Village, North Aceh Regency. capital The external side, on the other hand, looks at policies and commercial competition. This research employs a qualitative technique with descriptive analysis. Interviews, observation, and documentation were used to gather information. The informants included the Keuchik Gampong Cot Seurani, the owner of a sewing business that is not increasing, the owner of a sewing business that is growing, the People's Welfare Kaur, the Program Supervisor, and the Program Supervisor. The study's findings show that women's economic development efforts have been ineffective due to a lack of management and development capacity to operate their businesses and budget constraints. due to a lack of operating capital, policies, and fierce competition in the corporate world